Comprehensive Exploration of Biomedical Science in Transforming Global Health - Alsallum , Shakhis Daws D; Banihumayyim , Hadi Ali H; Alsallum , Mohammed Hussain M; Lasloum , Ahmad Hadi A; Alsallum , Salem Hussain M; Humayyim , Abdullah Khalid A; Algashaneen , Mana Abdullah A; Lsallum , Abdullah Saad M; Alsallum , Hamdan Hussain D; Lasloum , Ali Ahmad M; Alyami , Alyan Mohamad M (Journal of Ecohumanism, 2024)
Biomedical science has supervised tremendous changes in what the world considers health and how diseases are prevented, diagnosed, and treated. From the discovery of vaccines and diagnostic aids to innovations in genetics and genomic personalized medicine, spot the discipline as a key determinant of advancing the delivery and models of health Systems globally. This paper aims to review the effect of biomedical science on global health with a focus on retrospect and prospects of diseases, health, and crises. Thus, relying on up-to-date research, cases, and world health studies, the work reveals successes and failures. As for recommendations, they are to encourage innovation, extend the usage of biomedical technologies and involve individuals and disciplines expecting to make a positive change in the coming years that is stable and effective.Biomedical Science